2013
DOI: 10.1507/endocrj.ej13-0222
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological mechanisms involving aggressive islet cell destruction in fulminant type 1 diabetes [Review]

Abstract: Abstract. Fulminant type 1 diabetes is characterized by a rapid onset of severe hyperglycemia and ketoacidosis, with subsequent poor prognosis of diabetic complications. This review summarizes new findings related to the pathophysiology of accelerated β-cell failure in fulminant type 1 diabetes. Immunohistological examination revealed the presence of enterovirus in pancreatic islet cells and exocrine tissues and hyperexpression of pattern recognition receptors (PRRs) including melanoma differentiation-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…[27][28][29] A viral-induced immune reaction and cytokines are also suggested to play a role in the pathophysiology of the rapid destruction of pancreatic beta cells in FT1D, but there have been few reports on a specific role for IL-6 or IL-10 in the onset of FT1D. 30) These findings suggest that serial changes in serum cytokines in our patient might be partly explained by viral myocarditis. Additionally, although the underlying reasons were unclear, the decreases in IL-10 and IL-6 suggest that viral myocarditis accompanied by the onset of FT1D might become clinically evident with corrected ketoacidosis, even when ECG abnormalities are not detected before treatment of ketoacidosis.…”
Section: Discussionmentioning
confidence: 62%
“…[27][28][29] A viral-induced immune reaction and cytokines are also suggested to play a role in the pathophysiology of the rapid destruction of pancreatic beta cells in FT1D, but there have been few reports on a specific role for IL-6 or IL-10 in the onset of FT1D. 30) These findings suggest that serial changes in serum cytokines in our patient might be partly explained by viral myocarditis. Additionally, although the underlying reasons were unclear, the decreases in IL-10 and IL-6 suggest that viral myocarditis accompanied by the onset of FT1D might become clinically evident with corrected ketoacidosis, even when ECG abnormalities are not detected before treatment of ketoacidosis.…”
Section: Discussionmentioning
confidence: 62%
“…al. analyzed enterovirus-infected pancreatic specimens from subjects with fulminant diabetes and found that β-cells as well as a population of non-β-cells express IL-18 [28, 46]. Moreover, IL-18 mRNA is constitutively expressed in islet β-cells harvested from mice and rats [47].…”
Section: Discussionmentioning
confidence: 99%
“…5 Islet beta cell apoptosis occurs especially in the form of immune-mediated (Type 1) DM. 11 These models demonstrated that long-term hyperglycemia impairs renal structure and function.…”
Section: Introductionmentioning
confidence: 99%